Election Design Following Constitutional Court Decision Number 14/PUU-XI/2013 - Laksono, Fajar; Agustine, Oly Viana (The Constitutional Court of the Republic of Indonesia, 2016)
The major implication from Constitutional Court Decision No. 14/PUU-XI/2013 is that the Constitution promotes fundamental changes to the design of the general election regarding both process and substance. Therefore, in order to uphold the Constitution, efforts are required to reconstruct the design of the general election, particularly so that elections are conducted in accordance with Decision No. 14/PUU-XI/2013 as a representation of the spirit and the will of the 1945 Constitution. Essentially, the current norm regarding the implementation of general elections following the election of members of the representative institution is not consistent with the stipulations in Article 22E Paragraph (1) and Paragraph (2) and Article 1 Paragraph (2) of the 1945 Constitution. Constitutional Court Decision No. 14/PUU-XI/2013 aims to realign the implementation of the elections with the intentions of the 1945 Constitution. Through implementation of the original intent method and systematic interpretation, the Constitutional Court offered its interpretation that the framers of the amended Constitution intended that general elections have five ballot boxes, with the first for the Peopleâs Representative Council (Dewan Perwakilan Rakyat, DPR), the second for the Regional Representative Council (Dewan Perwakilan Daerah, DPD), the third for the president and vice president, the fourth for the Regional Peopleâs Representative Council (Dewan Perwakilan Rakyat Daerah, DPRD) at the provincial level and the fifth for the DPRD at the regency level. Thus, it can be concluded that the presidential elections should be conducted simultaneously with elections of members of the representative bodies. Through this decision, the Constitutional Court revoked the prevailing norm, such that Presidential Elections and Elections of members of representative bodies were no longer valid because they violated the 1945 Constitution. The Constitutional Court introduced a new legal condition that obligated General Elections to be held simultaneously.